Gene-Environment Interactions in Progressive Supranuclear Palsy - Litvan, Irene; Proudfoot, James A.; Martin, Eden R.; Standaert, David; Riley, David; Hall, Deborah; Marras, Connie; Bayram, Ece; Dubinsky, Richard M.; Bordelon, Yvette; Reich, Stephen; Shprecher, David; et al. (Frontiers in Neurology, 2021)
Several genetic and environmental factors have been reported in progressive supranuclear palsy (PSP), although none were identified as a definitive cause. We aimed to explore potential gene-environment interactions in PSP. 292 PSP cases and 292 controls matched for age, sex, and race from the ENGENE-PSP were analyzed to determine the association between PSP and minor alleles of 5 single nucleotide polymorphisms (SNPs) in 4 genes (MAPT, MOBP, EIF2AK3, and STX6), which were previously associated with PSP risk. Interactions between these SNPs and environmental factors, including previously reported occupational and agricultural risk factors for PSP, were assessed for PSP odds and age of symptom onset. Minor alleles of MAPTrs242557 and EIF2AK3rs7571971 were individually associated with increased odds; MAPTrs8070723 minor alleles were associated with lower PSP odds. There were several gene-environment interactions for PSP odds and age of symptom onset, however, they did not remain significant after FDR-correction. Larger scale studies are required to determine potential interactions.